Neurological Crises after Discontinuation of Nitisinone (NTBC) Treatment in 3 Cases of Tyrosinemia - Honar, Naser; Shakibazad, Nader; Serati Shirazi, Zahra; Dehghani, Seyed Mohsen; Inaloo, Soroor (Iranian Journal of Child Neurology, 2017)
Tyrosinemia Type 1 is a hereditary disorder with liver, kidney and nervous system involvement. We report 3 children developed diaphragmatic paralysis requiring mechanical ventilation after discontinuation of NTBC treatment. In patients with Tyrosinemia type 1, combined treatment with NTBC and a low-tyrosine diet have prevented neurological crises. Treatment with NTBC in the first months of life protects against hepatic and neurologic complications. Neurological crises can occur in tyrosinemia without treatment and also occur when treatment stops. We report three patients that developed diaphragmatic paralysis after interruption of NTBC treatment, which finally required mechanical ventilation. It should be emphasized that discontinuation of NTBC can induce diaphragmatic paralysis and respiratory failure. So we should advise patients to use NTBC for long term and not interrupted it.